Newly discovered circRNAs in rheumatoid arthritis, with special emphasis on functional roles in inflammatory immunity - Li, Zhenyu; Wang, Jianpeng; Lin, Yudong; Fang, Jihong; Xie, Kang; Guan, Zhiye; Ma, Hailong; Yuan, Liang (Frontiers in Pharmacology, 2022)
Circular RNA (circRNA) is a unique type of endogenous RNA. It does not have free 3 'or 5' ends, but forms covalently closed continuous rings. Rheumatoid arthritis (RA) is a common chronic autoimmune joint disease, characterized by chronic inflammation of the joint synovial membrane, joint destruction, and the formation of pannus. Although the pathogenesis of rheumatoid arthritis remains incompletely understood, a growing amount of research shows that circRNA has a close relationship with RA. Researchers have found that abnormally expressed circRNAs may be associated with the occurrence and development of RA. This article reviews the inflammatory immune, functions, mechanisms, and values of the circRNAs in RA to provide new ideas and novel biomarkers for the diagnosis and treatment of RA.